Analysis of serum cfDNA concentration and integrity before and after surgery in patients with lung cancer - Fan, Yihui; Shi, Minxin; Chen, Saihua; Ju, Guanjun; Chen, Lingxiang; Lu, Haimin; Chen, Jian; Zheng, Shiying (Cellular and Molecular Biology, 2019)
The content and integrity of cell-free DNA (cfDNA) before and after surgery in patients with lung cancer were determined to investigate its clinical significance. Peripheral blood was collected from 120 patients with lung cancer who were treated in our hospital from March 2016 to November 2018, including 50 cases before operation and 70 cases after operation. 60 healthy subjects served as controls. Quantitative PCR was used to determine the cfDNA level of each group. The relationship between cfDNA levels and the clinical features of lung cancer patients was determined. Receiver Operating Curves were used to determine the sensitivity and specificity of cfDNA, CEA, NSE and CYFRA21-1 in lung cancer. The concentration and integrity of cfDNA before surgery in patients with lung cancer were significantly higher than those after surgery and those in healthy control group. The cfDNA concentration in patients with lung cancer after surgery was significantly higher than that in the control group, but there was no statistical difference in cfDNA integrity between the two groups. There was no significant correlation between cfDNA concentration/integrity and gender, age, tumor type, tumor stage, and expressions of CA199, CA125, and CA153 in patients with lung cancer before or after surgery. However, there were significant correlations between the expression levels of CEA, NSE, and CYFRA21-1 and cfDNA concentration. The expression levels of CEA and CYFRA21-1 were significantly correlated with cfDNA integrity before surgery, while the correlations were not significant after surgery. The concentration and integrity of cfDNA increased significantly in serum of lung cancer patients. The concentration and integrity of cfDNA in patients with lung cancer after surgery were significantly lower than those before surgery. Thus, cfDNA has high application value in the diagnosis and evaluation of lung cancer.